2019
DOI: 10.1093/heapro/daz043
|View full text |Cite
|
Sign up to set email alerts
|

Co-production of a pictorial recovery tool for people with psycho-social disability informed by a participatory action research approach—a qualitative study set in India

Abstract: Mental health problems are recognized as a leading cause of disability and have seen increased allocations of resources and services globally. There is a growing call for solutions supporting global mental health and recovery to be locally relevant and built on the knowledge and skills of people with mental health problems, particularly in low-income countries. Set in Dehradun district, North India, this study aimed to describe first, the process of co-production of a visual tool to support recovery for people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…This requires shifting methods of engagement towards co-production 9 or participatory action research (PAR). Whilst, Randomised Control Trials using these approaches have shown positive impacts on improvements on other health conditions, such as diabetes 10 , more work is needed to address structural inequalities that may underpin co-production.…”
Section: Prioritizing Service User and Community Knowledge And Ownersmentioning
confidence: 99%
“…This requires shifting methods of engagement towards co-production 9 or participatory action research (PAR). Whilst, Randomised Control Trials using these approaches have shown positive impacts on improvements on other health conditions, such as diabetes 10 , more work is needed to address structural inequalities that may underpin co-production.…”
Section: Prioritizing Service User and Community Knowledge And Ownersmentioning
confidence: 99%
“…Community beliefs are largely ignored by mental health services in India and a previous study examining a “Programme for Improving Mental Health Care” (PRIME), a multiplatform multicomponent mental healthcare intervention in Madhya Pradesh for people with depression and alcohol use, suggested to increase contextually defined community-based care for better impact (Shidhaye et al, 2019). Going a step forward, psychosocial interventions could be built and implemented in partnership with the local community through an empowering approach (Mathias et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…41 Further programmes and research that examine how to build mental health literacy, engage positively with local knowledge and culture, and that seek to co-produce knowledge with people with lived experience in diverse Indian contexts is required. 43…”
Section: Contribution Of Lay Workersmentioning
confidence: 99%